Biogas improvement as renewable energy through conversion into methanol: A perspective of new catalysts based on nanomaterials and metal organic frameworks - Sánchez, Antoni (Frontiers in Nanotechnology, 2022)
In recent years, the high cost and availability of energy sources have boosted the implementation of strategies to obtain different types of renewable energy. Among them, methane contained in biogas from anaerobic digestion has gained special relevance, since it also permits the management of a big amount of organic waste and the capture and long-term storage of carbon. However, methane from biogas presents some problems as energy source: 1) it is a gas, so its storage is costly and complex, 2) it is not pure, being carbon dioxide the main by-product of anaerobic digestion (30%–50%), 3) it is explosive with oxygen under some conditions and 4) it has a high global warming potential (27–30 times that of carbon dioxide). Consequently, the conversion of biogas to methanol is as an attractive way to overcome these problems. This process implies the conversion of both methane and carbon dioxide into methanol in one oxidation and one reduction reaction, respectively. In this dual system, the use of effective and selective catalysts for both reactions is a critical issue. In this regard, nanomaterials embedded in metal organic frameworks have been recently tested for both reactions, with very satisfactory results when compared to traditional materials. In this review paper, the recent configurations of catalysts including nanoparticles as active catalysts and metal organic frameworks as support materials are reviewed and discussed. The main challenges for the future development of this technology are also highlighted, that is, its cost in environmental and economic terms for its development at commercial scale.